2022
DOI: 10.3389/fphar.2022.862085
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene in Combination With Mitochondrial Cofactors Improve Mitochondrial Function in Cellular Models of Mitochondrial Diseases

Abstract: Mitochondrial diseases are genetic disorders caused by mutations in genes in the nuclear DNA (nDNA) and mitochondrial DNA (mtDNA) that encode mitochondrial structural or functional proteins. Although considered “rare” due to their low incidence, such diseases affect thousands of patients’ lives worldwide. Despite intensive research efforts, most mitochondrial diseases are still incurable. Recent studies have proposed the modulation of cellular compensatory pathways such as mitophagy, AMP-activated protein kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…The mitochondrial respiratory function of control and mutant KAT6A fibroblasts were measured using a Mito stress test assay with an XF24 extracellular flux analyzer (Seahorse Bioscience, Billerica, MA, USA, 102340-100), according to the manufacturer’s instructions and previous studies [ 36 , 37 ]. Fibroblasts were seeded at a density of 1.5 × 10 4 cells/well with 500 µL of growth medium (DMEM medium containing 20% of FBS) in XF24 cell culture plates and incubated for 24 h at 37 °C with 5% of CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The mitochondrial respiratory function of control and mutant KAT6A fibroblasts were measured using a Mito stress test assay with an XF24 extracellular flux analyzer (Seahorse Bioscience, Billerica, MA, USA, 102340-100), according to the manufacturer’s instructions and previous studies [ 36 , 37 ]. Fibroblasts were seeded at a density of 1.5 × 10 4 cells/well with 500 µL of growth medium (DMEM medium containing 20% of FBS) in XF24 cell culture plates and incubated for 24 h at 37 °C with 5% of CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, itaconate, a metabolite derived from cis-aconitate, induces the mtUPR [ 90 ]. In addition, the activation of sirtuins by increased NAD+ levels also promotes the mtUPR, in particular, SIRT1 and SIRT3 activation [ 66 , 67 , 69 , 91 , 92 , 93 , 94 ]. Likewise, it was demonstrated that caloric restriction could activate the mtUPR via a miRNA-dependent pathway [ 95 ], and the treatment with statins, such as fluvastatin and rosuvastatin, that inhibit the 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase in the mevalonate pathway, activate the mtUPR since they interfere with mitochondrial electron carriers [ 96 ].…”
Section: Mitochondrial Proteostasismentioning
confidence: 99%
“…Mitochondrial diseases [60,64,73] Parkinson's disease [93][94][95][96]148] Alzheimer's disease [105][106][107][108][109] Huntington's disease [115] Amyotrophic lateral sclerosis [121][122][123][124] Heart diseases [132] Aging [139][140][141][142] Cancer [157,160] Author Contributions:…”
Section: Condition Related Studiesmentioning
confidence: 99%
“…It has recently been demonstrated that pterostilbene in combination with mitochondrial cofactors treatment activates SIRT3 and UPR mt as compensatory mechanisms, as well as enhances sirtuins’ levels and mitochondrial activity in several cell models of mitochondrial diseases [ 73 ]. In contrast to long-term antibiotic treatment, pterostilbene is considered safe for human consumption and presents numerous well-known features, such as a prominent antioxidant activity and a high anti-inflammatory potential [ 74 ].…”
Section: Mitochondrial Diseasesmentioning
confidence: 99%